2002
DOI: 10.1016/s0022-5347(05)64680-0
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Catheter Microwave Sterilization Techniques in a Single Clinic Population

Abstract: Significant variation exists in the cleaning and sterilizing techniques used by our patients, although they were given uniform written and verbal instructions. It is unclear from the data in the literature how this variation affects sterilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Microwave, boiling, and steam caused structural damage to some catheters. This was also found in the previous studies 9,17 where melting was observed and linked to the type of microwave used, with lower power domestic microwaves causing less widespread damage but affecting catheter rigidity. In the current study, large areas of the catheter, where the surface characteristics had been altered, were also clearly visible following steam sterilization.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Microwave, boiling, and steam caused structural damage to some catheters. This was also found in the previous studies 9,17 where melting was observed and linked to the type of microwave used, with lower power domestic microwaves causing less widespread damage but affecting catheter rigidity. In the current study, large areas of the catheter, where the surface characteristics had been altered, were also clearly visible following steam sterilization.…”
Section: Discussionsupporting
confidence: 81%
“…It concluded there was minimal change to the surface of a polyvinylchloride (PVC) catheter. In contrast, others, using microwave energy, referred to visual changes in flexibility but did not investigate further 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2008 national survey in Canada reported reuse of catheters by 47% of spinal cord patients whilst a 2013 Australian study reported reuse prevalence of 47–50% . Although policy changed in the USA in 2008 resulting in an increased provision of single‐use catheters, a 2013 survey indicates that 56% reuse their catheter a median of 20 times . Such variations without strong evidence to support or refute practice mean that there are no clear directions to clinicians on the superiority of one catheter practice over another with respect to UTI.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Although policy changed in the USA in 2008 resulting in an increased provision of single-use catheters, a 2013 survey indicates that 56% reuse their catheter a median of 20 times. [5][6][7] Such variations without strong evidence to support or refute practice mean that there are no clear directions to clinicians on the superiority of one catheter practice over another with respect to UTI. Three recent reviews have been conducted in an attempt to provide clinical guidance on best practice for intermittent catheterisation.…”
Section: Introductionmentioning
confidence: 99%